Analisis Nilai Guna dan Efektifitas Faktor Produksi Fibers Polyester di PT. QRS melalui Perbandingan Hasil Aktual dan Perhitungan - Lumayani, Puri; Suseno, Agustian (Fakultas Teknik Universitas Tulang Bawang, 2024)
In the industrial era 4.0, most of the production processes use automatic machines. However, not a few companies still carry out their production processes manually, for this reason it is necessary to carry out an analysis of the value of effectiveness and efficiency between the workforce and also the machines so that production runs well 0020GHIn writing this data and information obtained through interviews, observation, and documentation. This research uses descriptive method using a quantitative approach. Effective capacity of labor 1515.2. Whereas the effective capacity of the extruder machine is 378.8, the labor factor has not yet shown the maximum figure because it has not reached 100%. This can be seen from the average efficiency which only reaches 25%, while the efficiency of using extruder machines is maximized with the results of calculating an average efficiency of 100% per month, suggestions that explain the efficiency of the use of labor and machines. The results of the author's research at PT. QRS revealed that the condition of the low level of efficiency in the labor factor needs to be reviewed regarding the operation of the extruder machine which is still manual for the input of production raw materials. The efficiency of using the extruder machine at PT.QRS is already very good, it's just a matter of maintaining it. Keywords: Effectiveness and efficiency, production factors, Polyester fiber.